Application of conjugated materials in muscle movement recovery process - Zhang, Dengfeng; Fan, Guanxi (Frontiers in Chemistry, 2023)
Analyzing the application effect of conjugated materials in muscle motion recovery provides more reference for the practical application of conjugated materials in motion recovery, and also provides more basis for the wider application of conjugated materials. This article took students from a local college of physical education as the experimental subjects, and selected 38 students from the college who had sports muscle fatigue or injury for testing. This article randomly divided them into two groups: a research group and a control group, with 19 students in each group. The research group used the conjugated materials in this article for muscle movement recovery, while the control group used traditional methods for muscle movement recovery. This article tested the peak torque, total work, maximum radial displacement, and contraction time of two groups of students after initial exercise and muscle recovery. 80 hours after muscle movement recovery, the peak torque values of isometric contraction (264.59) and centripetal contraction (160.81) of the experimental group students were higher than those of the control group students (233.79) and centripetal contraction (130.43). The difference was statistically significant (P<0.05); the experimental group's isometric contraction time (30.02) and concentric contraction time (29.31) were also higher than the control group's isometric contraction time (27.31) and concentric contraction time (24.58), with statistical significance (P<0.05). Conjugated materials have an obvious effect on promoting the recovery of muscle movement. They not only help to increase the peak torque of isometric and centripetal contraction of muscles, but also increase the time of Muscle contraction and improve muscle quality.